Intervención Cognitivo-Conductual en Jugadores Mexicanos de Fútbol Profesional. Cognitive- Behavioral Intervention in Mexican Professional Soccer Players - Hebert Mercado Guerrero; Rebeca María Elena Guzmán Saldaña; Laszlo Egry Bulnes; Arturo del Castillo Arreola; Angélica Romero Palencia (European Scientific Journal, ESJ, 2017)
This pre-experimental study aimed to analyze the effects of a training program to improve athletic performance in soccer using cognitivebehavioral techniques during 12 sessions. The study involved 18 men professional players, with an average age of 19.50 years (DE=1.42). Athletic performance and the intervention included variables such as motivation, stress management, performance appraisal influence, mental ability and group cohesion that were evaluated through two applications (pre and post) of the “Psychological Characteristics of Sport Performance Questionnaire” (CPRD). A first analysis of the data showed no significant group differences between times of measurement; however, the Wilcoxon test yielded data that showed intra-individual changes in the variables mental ability and group cohesion. It’s important to point out that, the team won the championship after their participation in the intervention. The study reveals the importance of the psychologist work in the sports field.